Visual navigation and pedestrian spaces - Volichenko, Olga; Tsurik, Tatiana (project baikal, 2023)
Growing interest to the historical and cultural heritage and development of tourism actualizes the importance of information and communication means, which help to understand the existing urban landscape and increase the level of its comfort. A historical analysis of Kursk central streets has been made for this purpose. The authors consider the elements of pedestrian space structure as the basis for the arrangement of tourist route, as well as define the factors increasing their attractiveness. They give recommendations on how to form the urban interior with the use of design elements and creation of information and communication system in the context of the existing architectural appearance of Kursk city streets.